Beyond language - Antonio José Jiménez Muñoz (Ibérica, 2019)
Most universities now target graduate employability as an indicator of their educational self-efficacy. Undergraduate English-for-Specific-Purposes syllabi also include a number of market-wise soft skills such as presenting and negotiating as learner outcomes. However, ESP assessment remains languagebound. This study follows a quantification approach of the impact of multimodal factors in 140 recorded business pitches and 376 written investor reports. It provides statistical evidence of the impact of non-verbal elements on pitch success, revealing in turn an implicit conflation of non-verbal aspects and soft skills in academic assessment. Further analysis on the start-up valuation (a result of funds raised and equity released, in real-life terms) and their success factors (as justified in investor reports) makes it possible to infer that non-verbal elements are more directly related to pitch success than verbal aspects. A qualitative-quantitative analysis of investor reports confirms the minimal presence of linguistic elements as reasons for investment, and the primary focus on paralinguistic features to explain business decisions, which is the exact opposite to the reasons why ESP raters assign grades. In view of both these findings, it seems empirically evident that the theoretical problem posed by assessment discrepancy is indeed present: target soft-skills cannot be readily measured through grades and, conversely, grades do not necessarily reflect the acquisition of these skills. As a potential remedy, the need for a multimodal rubric-based improved method for assessment is put forward, so as to better align assessment and module targets expectations